Entropy Principle and Recent Results in Non-Equilibrium Theories - Vito Antonio Cimmelli; David Jou; Tommaso Ruggeri; Péter Ván (Entropy, 2014)
We present the state of the art on the modern mathematical methods of exploiting the entropy principle in thermomechanics of continuous media. A survey of recent results and conceptual discussions of this topic in some well-known non-equilibrium theories (Classical irreversible thermodynamics CIT, Rational thermodynamics RT, Thermodynamics of irreversible processes TIP, Extended irreversible thermodynamics EIT, Rational Extended thermodynamics RET) is also summarized.